2011
DOI: 10.1122/1.3570340
|View full text |Cite
|
Sign up to set email alerts
|

Large amplitude oscillatory shear flow of gluten dough: A model power-law gel

Abstract: SYNOPSISIn a previous paper [Ng and McKinley (2008)], we demonstrated that gluten gels can best be understood as a polymeric network with a power-law frequency response that reflects the fractal structure of the gluten network. Large deformation tests in both transient shear and extension show that in the absence of rigid starch fillers these networks are also time-strain factorizable up to very large strain amplitudes ( ). In the present work, we further explore the non-linear rheological behavior of these cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(72 citation statements)
references
References 61 publications
7
59
0
Order By: Relevance
“…LAOS parameters (e 3 /e 1 , v 3 /v 1 , G L , G M , h L , h M , S and T) showed that, the gluten network has time to stretch and reaches its limit in terms of its ability to elastically deform at the lower frequencies. These findings are consistent with Ng et al (2011) 0 s findings on gluten gels. We then studied Lissajous curves and we saw the previously observed intracycle strain thickening to occur with dough as well at all phases of Farinograph mixing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…LAOS parameters (e 3 /e 1 , v 3 /v 1 , G L , G M , h L , h M , S and T) showed that, the gluten network has time to stretch and reaches its limit in terms of its ability to elastically deform at the lower frequencies. These findings are consistent with Ng et al (2011) 0 s findings on gluten gels. We then studied Lissajous curves and we saw the previously observed intracycle strain thickening to occur with dough as well at all phases of Farinograph mixing.…”
Section: Discussionsupporting
confidence: 91%
“…Examples include gluten gels (Ng et al, 2011), polysaccharide dispersions i.e. carrageenan or starch (Klein et al, 2008), whey protein isolate and к-carrageenan gels (Melito et al, 2013a), tuna myofibrillar protein (Liu et al, 2014), commercial cheese (Melito et al, 2013b), and tomato paste (Duvarci et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The LAOS decoupling of simultaneous overall softening with local stiffening was also reported recently for a filled elastomer system [154]. Such physical insight may be able to inform constitutive models of this and other materials tested with LAOS, as recently demonstrated with nonlinear constitutive models to capture the biomechanics of hagfish gel [155] and gluten dough networks [156]. …”
Section: Biopolymer Gelsupporting
confidence: 68%
“…There have already been several examples in the rheology literature of studies focused on using LAOS to determine model parameters and test the predictive performance of constitutive models (Giacomin et al, 1993;Zhou et al, 2010;Calin et al, 2010;Ng et al, 2011;Giacomin et al, 2011;Gurnon and Wagner, 2012). Similarly, in the solid mechanics and plasticity community, experiments very similar to LAOS are frequently used to probe material behavior.…”
Section: Introductionmentioning
confidence: 99%